MODALITAS INTENSIONAL BAHASA REJANG - Siah, Fenny Tri; Winarti, Daru (Linguistik : Jurnal Bahasa dan Sastra, 2024)
The intentional modality is one of categories in modality as a universal language phenomenon having a variety of special markers. Each intentional modality marker is a lexicon in the form of a word or phrase. One lexicon represents one meaning, but it is different with lok having some meanings. This research is necessarily conducted to describe the forms and to analyze the meaning of the forms of the intentional modality markers in Rejang language clauses or sentences. In identifying the forms and classifying the meaning, it refers to Alwi's opinion through semantic studies. The qualitative descriptive method is carried out in this research through non-participant observation by marking clauses or sentences containing the intentional modality markers as data in Ireak Ca'o Kutei Jang's book explaining the customs of the Rejang tribe. The data is further analyzed to identify the forms. Thereafter, each marker is analyzed to classify its meaning depending on the intentional modality category. Based on the results, several markers of the intentional modality are found in the form of words: lok, maep, majok, maro, maroba, minoi, and tulung; phrases: minoi tulung, minoi maaf, and minoi izin filling the certain meaning, namely eagerness, hope, invitation, and request.